2020
DOI: 10.34302/crpjfst/2020.12.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Biologically Active Complex for Multifactorial Support Of the Central Nervous System: New Composition, Efficacy

Abstract: A new tablet form of biologically active food supplement for the multifactorial support of the central nervous system has been developed. It is named Supplement The supplement production technology prevents ingredients oxidative processes due to insignificant moisture content and exclusion of the active oxygen exposure. The biologically active complex facilitates memory retention and information retrieval, accelerates thinking process, and boosts the level of the overall energy potential by improving the centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In our contemporary, fast-paced environment dietary supplements are gaining popularity. Extensive studies have demonstrated that dietary supplements offer a gentle, but effective and long-lasting influence on metabolic processes; therefore, they are increasingly used to maintain good nutrition and health (Pokrovskij et al, 2002;Provalova et al, 2002;Zhdanov et al, 2005;Guryanov, 2010;Dorn et al, 2013;Dygai et al, 2013;Guryanov, 2013;Dorn et al, 2014;Mirmiran et al, 2014;Flodin et al, 2015;Vekovtsev et al, 2017;Buscemi et al, 2018;Zhang et al, 2018;Eksi et al, 2019;2020;Derbyshire et al, 2021;Sergun et al, 2021). Discussing dietary supplements produced with ingredients of animal origin, we would like to focus on antler supplements, in particular, pantohematogen.…”
Section: Introductionmentioning
confidence: 99%
“…In our contemporary, fast-paced environment dietary supplements are gaining popularity. Extensive studies have demonstrated that dietary supplements offer a gentle, but effective and long-lasting influence on metabolic processes; therefore, they are increasingly used to maintain good nutrition and health (Pokrovskij et al, 2002;Provalova et al, 2002;Zhdanov et al, 2005;Guryanov, 2010;Dorn et al, 2013;Dygai et al, 2013;Guryanov, 2013;Dorn et al, 2014;Mirmiran et al, 2014;Flodin et al, 2015;Vekovtsev et al, 2017;Buscemi et al, 2018;Zhang et al, 2018;Eksi et al, 2019;2020;Derbyshire et al, 2021;Sergun et al, 2021). Discussing dietary supplements produced with ingredients of animal origin, we would like to focus on antler supplements, in particular, pantohematogen.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, these conditions are often attributed to the disastrous civilization's impact on the environment; on the other hand, the food industry technology advances have introduced new food processing and preservation technologies, which might sometimes lead to the loss of essential nutrients in processed foods. Nutritional deficiency has an adverse health effect, causes the development of metabolic disorders and nutrient-related diseases, hinders the building of a healthier generation, and, eventually, might trigger social and economic losses (Pokrovskij et al, 2002;Boks et al, 2012;Mirmiran et al, 2014;Flodin et al, 2015;Chelnakova, 2016;Poznyakovsky et al, 2017;Rana & Paul, 2017;Vekovtsev et al, 2017;Garthe & Maughan, 2018;Tokhiriyon et al, 2019Tokhiriyon et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%